NFB-02. Maternal high-fat diet exposure increases the proliferation and glial differentiation of the cells of origin for NF1-optic glioma. (3rd June 2022) - Zhang, Kailong; Gutmann, David; Brossier, Nicole
Abstract: Some pediatric cancers arise in the context of tumor predisposition syndromes caused by germline mutations in genes that regulate cell growth. The most common of these syndromes, Neurofibromatosis type 1 (NF1), results in the development of low-grade tumors of the optic pathway (optic pathway gliomas; OPGs) in ~15% of affected children. However, risk assessment for each individual child is difficult, as it is currently challenging to predict which children with NF1 will develop OPG . Emerging human population-based evidence has raised the possibility that patient-specific risk factors, including infant birth weight, may modulate the risk of glioma development. High-infant birth weight can be modeled in mice by maternal exposure to a high-fat high-sucrose (HFHS) diet. To address the hypothesis that maternal high-fat diet exposure will increase the risk of OPG formation through intrinsic effects on the putative tumor cell of origin, we evaluated the effect of maternal exposure to a HFHS diet on the proliferation and differentiation of these cells (neural stem cells within the third ventricular zone; TVZ NSCs). Progeny from obese dams (MatOb) exposed to HFHS diet during and preceding gestation demonstrated increased proliferation and glial differentiation of TVZ NSCs in vivo . Similar results were observed with gestational HFHS diet exposure (GE) that did not result in maternal weight gain, suggesting these effects were related to maternal diet rather than weight. These effects were not observed in NSCs from other regions of the brain, supporting the regional specificity of the effect of diet on these tumor-initiating stem cells. Finally, we found that maternal HFHS diet resulted in elevated levels of leptin and insulin, both of which increase the proliferation of TVZ NSCs. Taken together, these findings provide early experimental evidence that maternal environmental exposure affects developing neural stem cells relevant to the risk of glioma formation.